UNPACKING THE DISCONNECT BETWEEN EDUCATIONAL INFRASTRUCTURE AND INSTITUTIONAL ATTRACTIVENESS - Kamarullah, Kamarullah; Nailah, Nasywaa Akeno; Akbar, Maulana; Alkhajaj, Pramugian; Rafiqi, Muhammad (Magister Manajemen Pendidikan, Universitas PGRI Semarang, 2025)
This study examines the internal perceptions of students and teachers regarding the limited institutional appeal of a public high school in Banda Aceh, Indonesia. Using a qualitative Grounded Theory approach, interviews with four students and two teachers revealed six major themes, including perceptions of academic quality, facility usage, teacher-student relationships, staff collaboration, external challenges, and proposed improvements. Findings highlight that despite adequate infrastructure, low student engagement, weak staff cohesion, limited competitiveness, and insufficient public promotion hinder the school’s attractiveness. Practical implications emphasize the need for integrated strategies combining academic improvement, community engagement, and institutional marketing. This research contributes to broader discussions on school improvement in post-disaster and decentralized education systems.